A dimensão relacional entre curadoria digital e metadados - Triques, Maria Lígia (Universidade Federal de São Carlos, 2020)
The amount and variety of data associated with cultural heritage have grown significantly in digital environments, generating a diversity of possibilities and challenges related to information representation, especially in studies focused on digital curation. In the Web environment, there is need for data informational treatment to take into account, in addition to all the stages through which they circulate, the ability to guarantee their informational purposes. In this scenario, digital curation is highlighted as an interdisciplinary activity that seeks to establish guidelines not only to maintain and preserve informational resources but also to ensure that data are continuously consistent with their informational purposes. To achieve this goal, digital curation adds value to data through the representation of information from metadata. Thus, this study questions how metadata influence digital curation actions and aims analyze the relationship between metadata and digital curation. This theoretical qualitative study was carried out through bibliographic survey and exploratory systematization, also using a documentary study of the Europeana platform to exemplifying digital curation and data representation, in this case, cultural heritage data made available on the Web environment. Results showed that digital curation seeks, through the process of adding informational value, to enrich data in such a way as to facilitate sharing and reuse. Therefore, it was found that metadata influence digital curation actions to the extent that these elements enable explanation of the semantic definitions necessary for communication within the management process, mainly in an automated way. In the end, the study about the Europeana platform provided the basis for the results, demonstrating how metadata, through instruments, principles, models and technologies, allows the semantic context of informational resources of cultural heritage to be ensured. In conclusion, the importance of metadata for digital curation is perceived not only as an essential factor to guarantee planning and execution of its actions, but mainly to allow digital resources to have their informational purpose assured and remain with quality and reliability for long-term access, use and reuse.
Relational dimension between digital curation and metadata
Keywords: Curadoria Digital; Metadados; Representação da informação; Web Semântica; Patrimônios culturais; Digital Curation; Metadata; Information representation; Semantic Web; Cultural heritage; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO